Early Main Group Metal Catalysts for Imine Hydrosilylation - Elsen, Holger; Fischer, Christian; Knüpfer, Christian; Escalona, Ana; Harder, Sjoerd (Chemistry - A European Journal, 2019)
The efficient catalytic reduction of imines with phenylsilane is achieved by using the potassium, calcium and strontium based catalysts [(DMAT)K (THF)]∞, (DMAT)2Ca⋅(THF)2 and (DMAT)2Sr⋅(THF)2 (DMAT=2-dimethylamino-α-trimethylsilylbenzyl). Eight different aldimines and the ketimine Ph2C=NPh could be successfully reduced by PhSiH3 at temperatures between 25–60 °C with catalyst loadings down to 2.5 mol %. Also, simple amides like KN(SiMe3)2 or Ae[N(SiMe3)2]2 (Ae=Ca, Sr, Ba) catalyze this reaction. Activities increase with metal size. For most substrates the activity increases along the row K
CRIS-Team Scopus Importer:2019-11-29
Keywords: alkaline earth metals; density functional calculations; hydrosilylation; imines; potassium

Ir(IV) Sulfoxide-Pincer Complexes by Three-Electron Oxidative Additions of Br-2 and I-2. Unprecedented Trap-Free Reductive Elimination of I-2 from a formal d(5) Metal - Frieß, Sibylle; Benyak, Anna; Herrera, Alberto Cesar; Escalona Bauza, Ana Melissa; Heinemann, Frank Wilhelm; Langer, Jens; Fehn, Dominik; Pividori, Daniel Maximilian; Grasruck, Alexander; Munz, Dominik; Meyer, Karsten; Dorta, Romano (Inorganic Chemistry, 2022)
Oxidative addition of 1.5 equiv of bromine or iodine to a Ir(I) sulfoxide pincer complex affords the corresponding Ir(IV) tris-bromido or tris-iodido complexes, respectively. The unprecedented trap-free reductive elimination of iodine from the Ir(IV)-iodido complex is induced by coordination of ligands or donor solvents. In the case of added I-, the isostructural tris-iodo Ir(III)-ate complex is quickly generated, which then can be readily reoxidized to the Ir(IV)-iodido complex with FcPF(6) or electrochemically. DFT calculations indicate an "inverted ligand field" in the Ir(IV) complexes and favor dinuclear pathways for the reductive elimination of iodine from the formal metal center.
CRIS-Team WoS Importer:2022-01-21

Tricyclic Sulfoxide-Alkene Hybrid Ligands for Chiral Rh(I) Complexes: The "matched" Diastereomer Catalyzes Asymmetric C-C Bond Formations - Nikol, Alexander; Zhang, Ziyun; Chelouan, Ahmed; Falivene, Laura; Cavallo, Luigi; Herrera, Alberto; Heinemann, Frank Wilhelm; Escalona, Ana; Frieß, Sibylle; Grasruck, Alexander; Dorta, Romano (Organometallics, 2020)
Deprotonation of phenyldibenzo[b,f]tropylidene (8) with LDA/t-BuOK followed by quenching with either diastereomer of inexpensive glucose-based t-Bu-sulfinate (R)- or (S)-11 affords a sulfoxide-alkene hybrid ligand as the diastereomeric pairs (SS,SC)-9/(SS,RC)-10 and (RS,RC)-9/(RS,SC)-10, respectively, which via chromatographic/recrystallization may be separated into the four isomers. The optically pure diastereomeric ligands (SS,SC)-9 and (SS,RC)-10 react with [RhCl(coe)2]2 to form the dinuclear complexes (RS,SC)-11 and (RS,RC)-12, respectively, in which the bidentate ligands coordinate the metal centers through the sulfur and alkene donor functions. These complexes catalyze the conjugate addition of arylboronic acids to cyclic Michael acceptors with enantioselectivities of up to 99% ee. DFT calculations show the preponderant influence of planar chirality of the ligand alkene function. The enantioselectivity switch observed between (RS,SC)-11 and (RS,RC)-12 is explained by the inverted cis-trans coordinations of the substrate molecules in catalytic steps.
CRIS-Team Scopus Importer:2020-04-03